CONSERVATION OF RAMMED-EARTH STRUCTURES: THE HISPANOCOLONIAL ARCHAEOLOGICAL SITE OF SANTA FE LA VIEJA, ARGENTINA - Calvo, Luis Maria (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The archaeological site of Santa Fe La Vieja in Argentina preserves the urban and architectural material record of the irst settlement of the city (1573-1660). All archaeological structures excavated since 1949 are of rammed earth, and correspond to the lower parts of the walls and foundations of the Council (Cabildo), three churches and dozens of houses. Since the irst excavations, the site was recovered for research and museum use, and various forms of protection and conservation were applied. Due to the loss of the original roofs and the vulnerability of the construction material to the action of environmental agents, the broadest and most controversial issues of design and erection of shelters to protect archaeological structures are questioned. In the case of Santa Fe La Vieja, from the time the remains of rammed earth walls were excavated, it was necessary to protect them from environmental agents, especially intense and frequent rainfall in some periods of the year. In parallel, the transformation of the site into an Archaeological Park has created demands for visitor access inside the protective shelters, as well as to guarantee its museological treatment. Finally, the inclusion of shelters in the context of a landscape with a strong presence of nature is another issue that should be taken into account when designing protective measures. The paper discusses conservation actions taken to date. The shelters that have been protecting the archaeological structures are evaluated, and current projects, which aim to achieve better protection, are presented.